Omni (Omni Publications International, 1978)
"OMNI was a science and science fiction magazine published in the US and the UK. It contained articles on science fact and short works of science fiction. The first issue was published in October 1978, the last in Winter 1995, with an internet version lasting until 1998." -Cf. Wikipedia article "Omni (magazine)" viewed Nov. 8, 2012.
Keywords: Science : Periodicals; Technology : Periodicals; Science fiction : Periodicals; Short stories : 20th century : Periodicals; DESARROLLO CIENTIFICO Y TECNOLOGICO : PUBLICACIONES PERIODICAS; TECNOLOGIA : PUBLICACIONES PERIODICAS; PUBLICACIONES PERIODICAS CIENTIFICAS